MULTIMEDIA PEMBELAJARAN AYO MENGENAL BILANGAN BERBASIS LEARNING CYCLE DI SEKOLAH DASAR - Rozie, Fachrur; Hani`ah, Hani`ah (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
The development and use of ICT learning media in the 21st century is very important to improve the quality of education. The learning process is an interaction between teachers and students and mutual feedback. The results of preliminary pre-research data conducted at SD Negeri Tanjung Jsati 2 Bangkalan found that in the learning process teachers only used media provided by the school and the government and used image media available around the school. The media used at school has incomplete material so that students are still less able to answer existing questions. Based on the problems above, researchers will develop interactive multimedia at SD Negeri Tanjung Jati 2 Bangkalan. This development uses a 4D development model with the learning cycle learning method. It is hoped that learning outcomes will be more interesting, students will not get bored in learning activities, and students will easily understand/learn each material. The results of the research conducted show that the multimedia let's get to know numbers obtained very decent expert validation results with a percentage of 91.5%, very interesting in terms of student response questionnaires with a percentage of 87.8%, and very effective in terms of student learning outcomes which reached 90.7% students complete.